Emotion modeling and Interaction of NPCS in Virtual Simulation and Games - Li, Ling; Campbell, James (IPI Press, 2010)
Virtual simulations and games utilizing NPC's, or computer controlled agents, are more predominant now that ever. Many of these simulations suffer from a lack of effective, stimulating, and natural emotion-based behaviours in the interaction among the NPC's, as well as with the human players. This paper presents an easy-to-use, portable, diverging, and adaptive emotion model based on psychological and sociological research, for simulation and game designers to utilize easily in their virtual world. The proposed emotino model allows the player to better relate, understand and believe in characters in the virtual environment.